Characterization and properties of calcium carbonate filled polypropylene (PP) / ethylene propylene diene terpolymer (EPDM) composites - Siti Rohana, Ahmad (Universiti Malaysia Perlis, 2010)
Composites of thermoplastic elastomer blend of polypropylene (PP) and ethylene propylene diene terpolymer (EPDM) reinforced calcium carbonate (CaCO3) was investigated. All the composites were prepared by using Z-blade mixer at 180oC and rotor speed 50 rpm. The effect of filler loading of calcium carbonate filled PP/EPDM composites on mechanical properties, water absorption, morphology and thermal properties were studied. In general, increased of calcium carbonate loading have increased the value of modulus of elasticity, water absorption, thermal stability, whereas tensile strength, elongation at break and crystallinity of composites reduced. A compatibilizer, (MAPP) or coupling agent, (3-APE) was used to improve the mechanical properties of composites. The presence of MAPP or 3-APE improved the tensile strength, modulus of elasticity, thermal stability and crystallinity composites, whereas elongation at break and water absorption reduced. Results from scanning electron microscope (SEM) show that fillermatrix interaction was improved with incorporation of MAPP or 3-APE. The effect chemical modification of calcium carbonate with acrylic acid (AA) in PP/EPDM composites increased the tensile strength, elongation at break, modulus of elasticity, thermal stability and crystallinity composite but water absorption reduced. The micrograph SEM showed the treated composites with acrylic acid has better dispersion in PP/EPDM matrix. Effects of dynamic vulcanization on the properties of PP/EPDM/CaCO3 composites exhibit higher tensile strength, elongation at break and modulus of elasticity but lower water absorption. The SEM study of tensile fracture surface of dynamic vulcanized composites show interfacial interaction between calcium carbonate and PP/EPDM matrix has been improved. The dynamic vulcanized composites also exhibit better thermal stability and higher crystallinity.